2017
DOI: 10.1371/journal.pone.0186055
|View full text |Cite|
|
Sign up to set email alerts
|

CT Chest and pulmonary functional changes in patients with HTLV-associated myelopathy in the Eastern Brazilian Amazon

Abstract: The aim of this study was to compare computed tomography (CT) scans of chest and lung function among patients with Human T-Lymphotropic Virus Type 1 (HTLV) with and without HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP). In this cross-sectional study performed between January 2013 and June 2016, we included 48 patients with HAM/TSP (19 women and 11 men) and without HAM/TSP (12 women and 6 men). We compared CT findings and lung functions of these groups. Patients who had HAM/TSP had abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
3
15
0
2
Order By: Relevance
“…The association between HTLV-1 infection and chronic lung disease is therefore recognised to have implications for staging of ATL [ 71 ]. Similar radiological findings have been reported in Brazil where bronchiectasis and centrilobular nodules were detected by HRCT in 14 of 30 patients with HAM but in only three of 18 asymptomatic controls with HTLV-1 [ 53 ].…”
Section: Clinical Studiessupporting
confidence: 86%
See 2 more Smart Citations
“…The association between HTLV-1 infection and chronic lung disease is therefore recognised to have implications for staging of ATL [ 71 ]. Similar radiological findings have been reported in Brazil where bronchiectasis and centrilobular nodules were detected by HRCT in 14 of 30 patients with HAM but in only three of 18 asymptomatic controls with HTLV-1 [ 53 ].…”
Section: Clinical Studiessupporting
confidence: 86%
“…Moreover, individuals with HTLV-1 associated bronchiectasis may not have been appropriately diagnosed and referred to the UK cohort at the time of this study because HTLV-1 testing has only recently been included in British national bronchiectasis guidelines [ 52 ]. A Brazilian case control study, which excluded causes of chronic lung disease other than HTLV-1, reported similar findings [ 53 ]. Abnormal results on CT chest were recorded for 22 of 30 patients with HAM, but only four of 18 controls with HTLV-1 who did not have HAM, and bronchiectasis was diagnosed in twelve and two patients with and without HAM, respectively [ 53 ].…”
Section: Epidemiological Studiessupporting
confidence: 53%
See 1 more Smart Citation
“…Persistent HTLV-1-mediated airways inflammation may therefore lead to progressive bronchial wall dilatation, and bronchiectasis. High rates of bronchiectasis among HTLV-1-infected Japanese adults[ 7 , 8 ], and associations between HAM/TSP and bronchiectasis in UK [ 28 ] and Brazilian cohorts [ 29 ] suggest that HTLV-1-associated bronchiectasis affects individuals of diverse genetic backgrounds infected with HTLV-1 strains other than HTLV-1c. Although HTLV-1 associated pulmonary disease in Japan is thought to be largely sub-clinical[ 14 ], published clinical details are limited and prospective survival studies have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…2020 ), skin ( Bimbi, Brzezinski, and Sokolowska-Wojdylo 2019 ; Schierhout et al. 2020 ), lungs ( Falcão et al. 2017 ; Dias et al.…”
Section: Introductionunclassified